Penentuan Tingkat Kritikalitas Peralatan Pembangkit Dengan Metode Equipment Criticality Management Dalam Rangka Penentuan Prioritas Pemeliharaan - SAPUTRA DWI NUGROHO (Sekolah Tinggi Teknik - PLN, 2021)
The criticality level of equipment used at PT PLN (Pesero) power plants at present is using the Maintenance Priority Index (MPI) method. The calculation for the criticality rating of MPI equipment uses 4 (four) types of calculations, namely SCR, OCR, ACR and AFPF. To add to the consideration in determining the priority of equipment maintenance, an additional calculation of the criticality level of PLTU Tarahan equipment is carried out using the Equipment Criticality Management method. The Equipment Criticality Management method has 4 (four) assessment perspectives, namely Production, Safety, Environment and Equipment Failure. Calculations that have been carried out on the top 100 (one hundred) equipment in the PLTU Tarahan SERP using the Equipment Criticality Management method, there are 85 (eight five) equipment that has “High” criticality and 15 (fifteen) equipment in the “Medium” criticality category. 15 (fifteen) equipment that has “Medium” criticality is equipment that has backup and part of common generating equipment.